DMA-based key generation method for IoT scenario - Yinuo HAO; Zhou ZHONG; Xiaoli SUN; Liang JIN (Tongxin xuebao)
Aiming at the problems of slow update frequency of channel key, low generation rate and limited node resources in the IoT scenario, a DMA-based physical layer key generation method was proposed, by using the agility and reconfigurability of DMA to improve the time variability and randomness of received signal.Firstly, DMA was used by the transmitter to randomly weight the signal and send it to the receiver, which could enhance the randomness of signals on the premise of ensuring the transparent reception of the signal.Then, the key from the received signal was extracted by the sender and receiver.By combining the rapid changeability and randomness of DMA, the randomness of signal source and the randomness of natural channel, a composite channel was constructed to improve the randomness of the key source.In addition, the channel estimation was transfered overhead from the terminal to the base station, which effectively reduced the overhead and delay of the communication system, and was suitable for IoT scenarios with asymmetric resources and lightweight equipment.Simulation results show that the proposed method can effectively improve the key generation rate in quasi-static scenarios, and the generated physical layer key has passed the NIST test.